2003
DOI: 10.1136/bjsm.37.2.179
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of large rotator cuff tears combined with instability in elite rugby football players

Abstract: Large rotator cuff tears are extremely uncommon in young people and when they occur they may be associated with shoulder instability. This paper reports on a series of six elite rugby union and rugby league footballers who presented with shoulder instability and large rotator cuff tears. They were treated with a two stage procedure: an open rotator cuff repair followed by an open shoulder stabilisation some 10 weeks later. All had successful outcomes. The paper also highlights the risk of tearing the rotator c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 9 publications
1
34
0
2
Order By: Relevance
“…The authors concluded that persistent pain and weakness after primary dislocation in this age group are indications for further evaluation. Similar presentations were noted by Goldberg et al [8] in a series of elite young rugby players. Five of the six participants had symptoms before a catastrophic injury, including difficulty with abduction and a sensation of a ''dead arm'' with forceful overhead muscular activity.…”
Section: Resultssupporting
confidence: 84%
See 4 more Smart Citations
“…The authors concluded that persistent pain and weakness after primary dislocation in this age group are indications for further evaluation. Similar presentations were noted by Goldberg et al [8] in a series of elite young rugby players. Five of the six participants had symptoms before a catastrophic injury, including difficulty with abduction and a sensation of a ''dead arm'' with forceful overhead muscular activity.…”
Section: Resultssupporting
confidence: 84%
“…In two of the studies, the absence of a capsulolabral lesion was specifically noted in all patients [3,27]. Four of the studies specifically included patients with a capsulolabral lesion and rotator cuff tear who underwent both an anterior stabilization and rotator cuff repair [8,11,32,42]. Mean outcomes (pain relief, Rowe shoulder scores, or American Shoulder and Elbow Society scores) improved in all studies, and redislocation was reported in only one study where two patients had irreparable cuff tears [32].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations